Pendekatan Sistematis Manajemen Risiko Terhadap Keberlanjutan UMKM di Kota Semarang Dengan Berbasis ISO 31000:2018 - Fajrul, Muh; Wahyono, Anang Tri; Kaharuddin, Erlitawati; Vernando, Alexander Nova (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In the business world, risk is an unavoidable aspect due to uncertainties that cannot be predicted, potentially leading to losses for companies, especially micro, small, and medium enterprises (MSMEs) with limited capital. These risks can disrupt operations, cause financial losses, and even result in bankruptcy. However, through effective risk management strategies, risks can be identified early, allowing for mitigation of their potential impacts. This study aims to identify the risk management processes along with the sources of risk, assess the risks that may arise, and analyze the strategies that MSMEs will implement to address or manage these risks in Semarang. The research is conducted in accordance with the risk management process (ISO 31000:2018), which includes risk identification, risk analysis, risk evaluation, and risk treatment. The results of the risk analysis identification reveal that MSMEs face various challenges, including economic uncertainty, changes in government policies, and fluctuations in raw material prices. A lack of capital, technology, and skilled human resources further hampers their competitiveness. This study identifies five main risks faced by MSMEs: capital risk, human resource risk, raw material risk, operational risk, and equipment risk. SWOT analysis aids in the identification and evaluation of these risks, highlighting that capital, human resource, and raw material risks require immediate management intervention due to their significant impact on operational sustainability. Risk treatment includes the implementation of effective emergency plans and the acquisition of modern technology. Ultimately, a collaborative approach involving government support and capacity building for MSMEs is recommended to ensure sustainable development and stability in facing these inherent business risks.